LF-SWIPT: Outage Analysis for SWIPT Relaying Networks Using Lossy Forwarding With QoS Guaranteed - Lin, Guiping; Zhou, Yike; Jiang, Weiwei; He, Xin; Zhou, Xiaobo; He, Guodong; Yang, Panlong (IEEE internet of things journal, 2022)
We analyze the outage performance of a lossy forwarding (LF) relaying system with the simultaneous wireless information and power transfer (SWIPT) capability. In the system of LF with SWIPT (LF-SWIPT), a source broadcasts its message to both a relay and a destination. A relay node with SWIPT functionality harvests energy and decodes information from the source signal. The energy is split into two parts for information processing and message forwarding, respectively. For information processing, the relay attempts to decode the incoming source signal and forms an estimate. Unlike the existing decode-and-forward SWIPT system (DF-SWIPT), the estimate is always forwarded using the harvested energy. The destination performs joint decoding to recover the message with the signals received from both the source node and the relay node. We derive the outage probability for the LF-SWIPT system based on the theorem of source coding with side information . The simulation results demonstrate that the proposed system achieves significant gains (around 1-2 dB) compared to the DF-SWIPT system. We further evaluate the impact of the distance and the power splitting (PS) strategy on the system performance using simulations. Finally, we build an optimization algorithm on the PS ratio by maximizing the admissible region from the theoretical perspective.